Physiological and biochemical responses of olive tree to potassium supply under rainfed conditions - Silva, Ermelinda (2019)
Olive tree has a relevant economic, social, cultural and environmental importance in the Mediterranean region. Although the crop is modest in mineral nutrition requirements, the physiological and biochemical processes respond positively with a balanced mineral nutrltion reglme. The study, conducted in Bragança (Northeast Portugal), beganin2013 in a 3-year-old olive grave, witht wo treatments(applicationof133gKtree-1yr1 and without K). After a period of 3 years in which there were no significant physiological and biochemical effects, the results during2017 and winter 2018 show ed that supply ameliorate olive tree physiological performance, as indicated by higher net photosynthetic rate, dueto lower stomatal and non-stomatal limitations, the last more evident in winter measurements in a elose association with higher intrinsic water use efficiency, and superior relative water content, as well as higher concentrations of leaf total soluble proteins and soluble sugars, both in leave sand branches.